Comparative Analysis of Amateur and Professional Boxing: Organizational Aspects - Bekjanova Shakhinabonu Baxrom qizi (Zien Journals, 2023)
The practical significance of the study is that as a result of the pedagogical observations carried out, the main differences between amateur and professional boxing competitions were identified
Keywords: IBA; WBA; IBF; WBC